Direct synthesis of 6-sulfonylated phenanthridines via silver-catalyzed radical sulfonylation-cyclization of 2-isocyanobiphenyls. Issue 33 (15th August 2018) - Singh, Manjula; Yadav, Arvind K.; Yadav, Lal Dhar S.; Singh, Rana Krishna Pal
Graphical abstract: Highlights: Direct synthesis of 6-alkyl/arylsulfonyl phenanthridines. Silver-catalyzed sulfonylation with sodium sulfinates. Sulfonyl radical triggered cyclization-aromatization of 2-isocyanobiphenyls. Use of K2 S2 O8 as a radical surrogate and oxidant. Abstract: A convenient and straightforward synthesis of 6-sulfonylated phenanthridines via silver-catalyzed sequential radical insertion, cyclization and aromatization of 2-isocyanobiphenyls is reported. The protocol does not require a phenanthridine scaffold as a substrate and presents a highly regioselective synthesis of 6-alkyl/arylsulfonyl phenanthridines. The protocol utilizes readily available and easy to handle sodium sulfinates as sulfonating agents and potassium persulfate as an oxidant to afford good to excellent yields of the desired products in a one-pot operation at room temperature.